Strategi percepatan persiapan dokumen zona integritas di lingkungan Pascasrajana Universitas Jambi - Eliyanti; Indryani, Indryani; Aditya Candra, Alif; Putra, Iwan; Pathoni, Haerul; Muji Rahayu, Dyah; Sari, Nurmala (Proceedings Academic Universitas Jambi, 2025)
The development of an Integrity Zone (ZI) serves as a pilot initiative to promote bureaucratic reform aimed at enhancing governance quality, accountability, and integrity while preventing corruption. At the Postgraduate Program of Universitas Jambi, the implementation of ZI encountered challenges, including limited understanding of indicators, inconsistent document quality, and weak cross-unit coordination. This study employed a descriptive qualitative approach through literature analysis to formulate strategies for accelerating ZI document preparation, identifying supporting and inhibiting factors, and designing a document management system. Findings indicate that the ZI Development Working Team was formally established through Rector’s Decree No. 073/UN21/OT/2025, and the three-stage acceleration strategy significantly improved readiness (35% in first phase, 78% in second phase , and over 90% in third phase). The outcomes highlight the effectiveness of the strategy and the importance of staff participation. Supporting outputs include a policy brief, action plan, and academic manuscript. Overall, the ZI development has strengthened transparency, accountability, and service quality within the Postgraduate Program, emphasizing the need for synergy, technology-based innovation, and continuous evaluation